Low-penetrance R92Q (p.Arg121Gln) mutation in the TNFRSF1A gene: the significance and variants of phenotypes. Successful experience with the interleukin-1 inhibitor canakinumab in a female patient, who is a carrier of R92Q mutation with a severe TRAPS phenotype - E. S. Fedorov; S. O. Salugina; E. Yu. Zakharova; E. A. Kamenets; A. N. Gerasimenko (Современная ревматология)
The paper is devoted to the assessment of the R92Q (p.Arg121Gln) mutation/polymorphism in the TNFRSF1A gene associated with the monogenic autoinflammatory disease – Tumor Necrosis Factor Receptor-Associated Periodic Syndrome (TRAPS). It gives data on the frequency of this gene in the general population, which is 1.3% and significantly exceeds the incidence of TRAPS. The authors describe the variants of phenotypes associated with its mutation from asymptomatic carriage to the development of a severe systemic autoinflammatory state with persistent febrile fever and a significant increase in the level of acute-phase inflammatory markers that do not respond to standard antirheumatic therapy. They present a clinical case of the high efficiency of the anti-interleukin 1β monoclonal antibody canakinumab in a female patient with a severe TRAPS phenotype, who had the R92Q mutation and hormonal dependence. Canakinumab therapy led to complete relief from all manifestations of the disease and to discontinuation of glucocorticoids. The authors conclude that the decision to prescribe therapy with biological agents should be made on the basis of the clinical severity of the disease rather than a variant of the mutation that caused it.